(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the study is to substantiate the theoretical and methodological provisions and develop practical recommendations for the development of green entrepreneurship for the post-war recovery of Ukraine based on the experience of Latvia. The scientific novelty of the study lies in solving an important scientific and applied task - further development of theoretical aspects of green entrepreneurship, substantiation of the relationship between eco-innovation, green growth strategies and environmental policy in the context of sustainable development. The study uses general scientific and special methods: scientific abstraction, deduction, analysis and synthesis, systemic and critical analysis, structural and logical, ascent from the abstract to the concrete, and statistical analysis. It is proved that the Latvian business ecosystem is adapted for highly efficient investments and innovations in the field of green technologies. The study identified guidelines for environmental policy that will promote the development of green entrepreneurship, increase the density of green infrastructure, extend the life cycle of high value-added products manufactured in the country, reduce waste and encourage recycling. The importance of studying the experience of Latvia in strengthening the strategic framework for sustainable development and green growth for the post-war recovery of Ukraine is substantiated. It is determined that improving the quality of environmental infrastructure and services, as well as investing in innovation potential, will ensure the decoupling of economic growth from resource use and environmental depletion and accelerate the transition to a closed-loop economy. The authors propose the components of a «green» post-war recovery of Ukraine in the context of its further European integration.